Restructuring Organization of Dieng Farm Woekers When Tobacco to Potato - Samderubun, Godefridus; Izdiha, Anis; Mamlakah, Arin (Department of Sociology Faculty of Social and Political Sciences, 2023)
Dieng people who initially planted tobacco as a major agricultural commodity began to shift to potato commodities because of a faster, more effective harvest and offered more 'promising' results than tobacco. This new orientation by the potatoes opens up the opportunity for this change of new production organization arrangement for dieng community with two commodities namely tobacco and potato. This paper aims to provide a detailed picture of how these commodity changes affect the work structure of the agricultural system in Dieng.Methods of data collection were conducted by observation and in-depth interviews on five potato farmers and tobacco farmers who survived. This research was conducted in Campursari Village, Dieng Sub-district, Wonosobo Regency in June-July 2012. The findings of this study indicate that commodity changes from tobacco to potatoes lead to changes in production work structure and marketing chain, changes in work structure also change the economic order in each sub-performers on the production unit. Opportunities for the emergence of middlemen and skipper are increasingly prompted to create new social classes or new rich people. Nevertheless, there are rationality choices that develop in society about tobacco that still leaves room for workers to work. This rationality also encourages the existence of Dieng agriculture with two main commodities. Keyword: Economic Restructuring, Rationality, Dieng, Tobacco, Potato.